Association of Engineering and Shipbuilding Draughtsmen - Notes made from wireless bulletins (?) (page 17)
"Association of Engineering and Shipbuilding Draughtsmen - Notes made from wireless bulletins (?) (page 17)" [g0973017.jpg], n.d.